PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS POP UP BOOK MATERI PERUBAHAN CUACA PADA SISWA KELAS III SD - Dina, Dina; Lubis, Patricia H.M; Ramadhani, Erfan (Faculty of Teacher Training and Education, 2024)
The use of learning media is still very limited to science subjects in grade III elementary school. Therefore, it is necessary to develop pop-up book-based science learning media. This research aims to develop science learning media based on pop up books on weather changes for third grade elementary school students in order to determine the criteria for validity and practicality. Validity criteria are carried out by material experts, media experts and language experts. Meanwhile, practicality is carried out by teacher responses and student responses through questionnaires. This research uses the R&D method with Branch theory, namely the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The research was conducted at SD Negeri 95 Palembang. The validation results by the validator obtained an average score of 90.22% with a very valid category. The practicality results of the teacher response questionnaire obtained an average of 92% and students in the one to one trial with an average score of 91.5% and the small group trial with an average of 90% in the very practical category. From the results of these data, it can be concluded that the development of science learning media based on pop up books regarding weather changes for third grade elementary school students is categorized as very valid and very practical so it is suitable for use in achieving learning goals in schools.